2022
DOI: 10.1002/ep.13975
|View full text |Cite
|
Sign up to set email alerts
|

Experimental comparison of solar thermal desalination systems based on energy, exergy and economic (3‐E) analysis

Abstract: With rapid increase in human population, the demand of fresh water has been increased significantly and the world will encounter enormous water crisis by 2040.The sea contains nearly 97% of available water on earth. To fulfill the demand of fresh water, desalination of sea water can be best solution. As desalination process can be performed by using low grade energy, the use of solar energy for desalination is very popular. The most popular solar thermal desalination system is conventional solar still but its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…To harness the solar energy, solar collectors like flat plate collector (FPC), and evacuated tube collector (ETC) are used. 7 The FPC is mostly used for low temperature range application due to its simplicity, easy operation, less maintenance and low price. Vengadesan and Senthil 8 reviewed the various advancement in the field of flat plate solar air heater (FP-SAH), it was observed that by using inserts, baffles, and turbulators, the performance of FP-SAH was increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To harness the solar energy, solar collectors like flat plate collector (FPC), and evacuated tube collector (ETC) are used. 7 The FPC is mostly used for low temperature range application due to its simplicity, easy operation, less maintenance and low price. Vengadesan and Senthil 8 reviewed the various advancement in the field of flat plate solar air heater (FP-SAH), it was observed that by using inserts, baffles, and turbulators, the performance of FP-SAH was increased.…”
Section: Introductionmentioning
confidence: 99%
“…Solar energy can be used for producing hot air. To harness the solar energy, solar collectors like flat plate collector (FPC), and evacuated tube collector (ETC) are used 7 . The FPC is mostly used for low temperature range application due to its simplicity, easy operation, less maintenance and low price.…”
Section: Introductionmentioning
confidence: 99%
“…This process exploited the benefits of carbon dioxide and presented an exergy efficiency of 31.4%. In desalination, Kumar et al 29 compared the performance of a conventional solar desalination system with a new desalination system based on evacuated tube collectors (ETC). It was observed that ETC desalination has a higher average exergy efficiency than the conventional model and was evaluated at 9.52%.…”
Section: Introductionmentioning
confidence: 99%